Parasexual genetics of Dictyostelium gene disruptions: identification of a ras pathway using diploids - Insall Robert H; King Jason (BMC Genetics, 2003)
Abstract Background The relative ease of targeted gene disruption in the social amoeba Dictyostelium has stimulated its widespread use as an experimental organism for cell and developmental biology. However, the field has been hamstrung by the lack of techniques to recombine disrupted genes. Results We describe new techniques for parasexual fusion of strains in liquid medium, selection and maintenance of the resulting stable diploid strains, and segregation to make recombined haploids. We have used these techniques to isolate rasS/gefB double nulls. The phenotypes of these mutants are no more severe than either parent, with movement, phagocytosis and fluid-phase endocytosis affected to the same degree as in rasS or gefB single nulls. In addition, we have produced diploids from one AX2- and one AX3-derived parent, providing an axenic strain with fewer secondary phenotypes than has been previously available. Conclusions The phenotype of the rasS/gefB double mutant suggests that the RasS and GefB proteins lie on the same linear pathway. In addition, axenic diploids and the techniques to generate, maintain and segregate them will be productive tools for future work on Dictyostelium. They will particularly facilitate generation of multiple mutants and manuipulation of essential genes.